30.3k views
2 votes
What is 2(x+3)=x-4
(working out shown)

User Meze
by
5.3k points

2 Answers

5 votes

2(x+3)=x-4 is our original equation and we want it solved for x. Order of operations, or PEMDAS, tells us to work with the parentheses on the left first.

2(x + 3) = x - 4

2x + 6 = x - 4 <-------multiply by 2 on the left side, for both terms

2x = x - 10 <--------subtract 6 on both sides

x = -10 <--------subtract x on both sides


Thus x = -10

User Maxfax
by
6.0k points
2 votes

Equation step-by-step:

2(x + 3) = x - 4 → we use the distributive property

2x + 6 = x - 4 → we take + 6 to the right side of the equation

2x = x - 4 - 6 → we solve for - 4 - 6

2x = x - 10 → we take x to the left side of the equation

2x - x = - 10 → we solve for 2x - x

x = - 10 → final answer



Hope it helped,


BioTeacher101

User Iamthestreets
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.